Pengabdian Kepada Masyarakat Sistem Cerdas Perlindungan Pratima Pura di Kabupaten Bangli Berbasis Deteksi Citra dan RFID - Made Sudarma; Ni Wayan Sri Ariyani; I Putu Agus Eka Darma Udayana; Yogiswara Dharma Putra; I Gede Totok Suryawan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Pratima is a sacred symbol in Balinese Hindu belief, holding high spiritual value and serving as a medium of worship in temples (pura). The increasing number of pratima thefts has caused not only material losses but also immaterial impacts due to the loss of their sanctity. This activity aims to develop and implement an intelligent system based on Radio Frequency Identification (RFID) and image detection technology for real-time monitoring and tracking of pratima in Desa Adat Bebalang, Bangli Regency. The system integrates long-range RFID with the Centroid Localization Algorithm and AI-based smart CCTV (VGG16), which can detect suspicious activity and automatically send notifications to the mobile application used by traditional security personnel. The program includes site mapping, equipment installation, training, trial implementation, and participatory evaluation with local communities and the Bendesa Adat. The results show that the system operates reliably, accurately, and is user-friendly. Evaluation data indicate that most respondents agreed or strongly agreed with the system’s usefulness. The system is technically effective and culturally accepted, with potential for replication in other temples across Bali. This initiative demonstrates that the integration of modern technology and local wisdom can offer sustainable solutions for the preservation and protection of cultural heritage.